2011
DOI: 10.17705/1thci.00033
|View full text |Cite
|
Sign up to set email alerts
|

Team Climate and Media Choice in Virtual Teams

Abstract: As work teams become more distributed, effective computer-mediated communication is increasingly impacting their performance. This study investigates how team climate influences communication frequency among team members and their use of different communication media. Data were collected in two information systems courses offered at an Austrian university in which 50 student teams developed web-based applications and conducted usability tests. A team climate framework based on task and social orientation was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…ICT enables VT members to access, store, retrieve, and exchange information across time and space boundaries [57,58]. Furthermore, communication through technological tools can be registered, duplicated, and repeated at any time by any team member around the world [51,59,60]. Finally, the ability to electronically capture, store, and retrieve the team's process and outcomes contributes to the organizational knowledge and learning development, and ultimately may increase VT effectiveness [58,61].…”
Section: Technology-mediated Communicationmentioning
confidence: 99%
“…ICT enables VT members to access, store, retrieve, and exchange information across time and space boundaries [57,58]. Furthermore, communication through technological tools can be registered, duplicated, and repeated at any time by any team member around the world [51,59,60]. Finally, the ability to electronically capture, store, and retrieve the team's process and outcomes contributes to the organizational knowledge and learning development, and ultimately may increase VT effectiveness [58,61].…”
Section: Technology-mediated Communicationmentioning
confidence: 99%
“…When communication processes are aligned with technology, outcomes are generally expected to be positive (DeSanctis & Poole, 1994). But it can be hard to match technology to a task because some media are more suitable for particular work than others (Figl & Saunders, 2011). For example, research on military training found that alternatives such as text-based chat may fall short in providing critical verbal and gestural communication cues such as uncertainty and urgency that are clearly available in face-to-face contexts (Budlong, Walter, & Yilmazelb, 2009).…”
Section: Communicationmentioning
confidence: 99%
“…However, the intensive use of CT also imposes major challenges. While technology usage encompasses certain impediments [5], CT further causes interpersonal interactions implying challenges for the human brain and human behavior. The Harvard Business Review even circumscribes these with a "Collaborative Overload" [2].…”
Section: Introductionmentioning
confidence: 99%